An empirical study of the relationship between assignment practices in training programs and training motivation - Rafiuddin, N.M.; Ismail, A.; Ghazali, M.Z.; Ismail, Yusof; Mohamad Faudzi, Mohd Hasbullah; Arshad, M.M. (Medwell Publishing, 2012)
The purpose of this study was to measure the relationship between training assignment and training motivation using self-report questionnaires collected from cadet officers in a military training academy, Malaysia. The outcomes of testing hypothesis using a stepwise regression analysis showed two important findings; firstly, mandatory assignment is significantly correlated with training motivation. Secondly, voluntary assignment is also significantly correlated with training motivation. This result demonstrates that training assignment practices act as important predictors of training motivation in the studied organization. In addition, this study elaborates discussion, implications and conclusion.